Automated Monitoring of Human Physiological Parameters While Being in Virtual Reality - S. V. Mazur; A. I. Golovaty (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
A study was conducted on the control of a person’s pulse in the normal state and while in virtual reality. It has been established that a person’s pulse can increase significantly when he is in virtual reality. In this case, there may be various stressful situations, during which the pulse sharply quickens several times. In the process of research, a person’s pulse was predicted based on several machine learning models, which made it possible to predict a person’s condition in the near future and coordinate a series of actions to prevent risks. The most suitable models were linear regression and SSA, which showed the most accurate and plausible results. By monitoring the human heart rate in virtual reality, virtual reality scenes can be classified according to the degree of their effect on the human body. This allows to take into account people with various chronic diseases and to limit their access to scenes that are contraindicated for them. The result of the research was a software package that allows to continuously collectheart beat rate data while in virtual reality from a Bluetooth Low Energy device.